Bryozoan diversity in the Mediterranean Sea: an update - ROSSO, A.; Di MARTINO, E. (Mediterranean Marine Science, 2016)
This paper provides a current view of the bryozoan biodiversity of the Mediterranean Sea updating the checklist by Rosso (2003). Bryozoans presently living in the Mediterranean increase to 556 species, 212 genera and 93 families. Cheilostomes largely prevail (424 species, 159 genera and 64 families) followed by cyclostomes (75 species, 26 genera and 11 families) and ctenostomes (57 species, 27 genera and 18 families). Few families and genera make the bulk of this biodiversity whereas one third of families are monospecific. The number of species-rank taxa has increased by 81 in the last dozen years but most of these additions relate to the revision of material from old collections and to the introduction of non-indigenous species. Most of the bryozoan diversity is distributed in the coralligenous and dark and semi-dark cave biocoenoses followed by detritic bottoms. Diversity lowers in shallow-water vegetated bottoms and in bathyal habitats. Further increase in diversity is expected from investigation of still poorly known areas and habitats and the need for rapid assessment is remarked on in view of the management of Mediterranean habitats through the EU Marine Strategy Directive.